Analisis Wilayah Potensi Ubi Kayu - Dayu Nur Angga Nur Angga; untari untari; Maria Maghdalena Diana Widiastuti (Musamus Journal of Agribusiness, 2019)
Merauke Regency is a relatively large agricultural area that has not been widely used so that the potential for the growth and development of cassava plants. Besides cassava has many benefits both for daily needs to be used as a raw material for many processed products. This study aims to determine the potential of the base area and the characteristics of the spread of cassava commodities in Merauke Regency. The study was conducted in 13 districts (districts). This type of research is descriptive research. This research uses purposive sampling. Analysis of the data used is Location Quotient (LQ), localization coefficient and specialization analysis. Cassava commodity base districts with harvest area indicators are Sota, Ulilin, Animha, Jagebob, Kimaam, Okaba, Elikobel, Naukenjerai and Merauke Districts. Cassava commodity base districts with indicators of total production are Sota, Ulilin, Jagebob, Kimaam, Animha, Elikobel, Okaba and Naukenjerai Districts. The characteristics of the distribution of cassava commodity farming activities with a positive localization coefficient value is 0.5966 and there are six districts that have a positive localization coefficient each year, namely the Districts of Kimaam, Okaba, Naukenjerai, Jagebob, Sota and Elikobel. Districts that have positive specialization coefficient values ​​specialize one of their agricultural activities in cassava commodities with an average value of specialization coefficient of more than one, namely 1.3088 and an increase in the value of specialization coefficient each year. Keywords: Area analysis; cassava; potential; Location Quotient (LQ)